A Study Assessing Anxiety Levels Among Adolescents Who Attained Early Menarche Using Generalised Anxiety Disorder - 7 Scale (Gad-7) - Harshinee N, Harshinee N; Selvam, Vidhya; Meena, T. S.; Kaavya M, Kaavya M (Journal of Neonatal Surgery, 2025)
Background: Early menarche, defined as menstruation onset between ages 8 and 10, is increasingly linked to psychological distress, particularly anxiety, in adolescent girls. Limited data exist on this issue in India, where cultural and social factors may amplify risks. This study assesses anxiety levels among adolescent girls in Chennai with early menarche using the Generalized Anxiety Disorder-7 (GAD-7) scale. Objective: To evaluate the prevalence and severity of anxiety among adolescent girls aged 10–19 years who experienced early menarche and identify associated risk factors, such as age at menarche and menstrual irregularity. Methods: A cross-sectional study was conducted from March to May 2025 in Chennai schools, involving 170 girls aged 10–19 years with menarche between ages 8 and 10, selected via purposive sampling. Anxiety was measured using the GAD-7 scale, with severity categorized as minimal (0–4), mild (5–9), moderate (10–14), and severe (15–21). Data on demographics and menstrual history were collected via self-administered questionnaires. Associations between anxiety, age at menarche, and menstrual regularity were analyzed using statistical tests (p < 0.05). Results: Of the 170 participants, 55.8% (n=95) reported anxiety symptoms: 29.4% mild, 17.6% moderate, and 8.8% severe. Additionally, 26.5% had minimal anxiety, and 17.6% reported no anxiety. Earlier menarche (8–9 years) was significantly associated with higher moderate and severe anxiety compared to menarche at 9–10 years (p < 0.05). Menstrual irregularity strongly correlated with increased moderate and severe anxiety (p < 0.01). Conclusion: Over half of the adolescent girls with early menarche experienced anxiety, with earlier onset and menstrual irregularity as significant risk factors. These findings highlight the need for targeted mental health interventions and menstrual health education in Indian schools.